Perancangan Interior Café Thematic di Surabaya - Jessica Audrey; Mariana Wibowo; Poppy Firtatwentyna Nilasari (Intra, 2020)
The design of this cafe is aimed at all walks of life (small children, young people, parents). The main purpose of design is to produce a unique cafe design that is themed and uses aspects of universal design. The specific purpose of designing this cafe is to provide facilities to the community as a comfortable, attractive hangout, making visitors who are there become relaxed. And this cafe is designed with a different design from other cafes located in Surabaya to attract visitors in Surabaya and outside Surabaya to come to this cafe. The method used in designing this café is design thinking which consists of 10 stages, namely, discovery, observe , emphatize, leverage stories to discover insights, frame and reframe, ideate, decide, prototype, validate your ideate, iterate. Design results in the form is in the form of data collection by field surveys, design experiments, work drawings, study mockups, prototypes, documentation, mood boards, etc.